Unethical for the sake of the group: Risk of social exclusion and pro-group unethical behavior - THAU, Stefan (Institutional Knowledge at Singapore Management University, 2015)
This research tested the idea that the risk of exclusion from one's group motivates group members to engage in unethical behaviors that secure better outcomes for the group (pro-group unethical behaviors). We theorized that this effect occurs because those at risk of exclusion seek to improve their inclusionary status by engaging in unethical behaviors that benefit the group; we tested this assumption by examining how the effect of exclusion risk on pro-group unethical behavior varies as a function of group members' need for inclusion. A 2-wave field study conducted among a diverse sample of employees working in groups (Study 1) and a constructive replication using a laboratory experiment (Study 2) provided converging evidence for the theory. Study 1 found that perceived risk of exclusion from one's workgroup predicted employees' engagement in pro-group unethical behaviors, but only when employees have a high (not low) need for inclusion. In Study 2, compared to low risk of exclusion from a group, high risk of exclusion led to more pro-group (but not pro-self) unethical behaviors, but only for participants with a high (not low) need for inclusion. We discuss implications for theory and the management of unethical behaviors in organizations.